Utilization of Prezi in Learning Media Management to Increase the Effectiveness of Teaching and Learning Activities - Swandari, Wiwin; Saryanto, Saryanto; Rejokirono, Rejokirono (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Education is a learning process that involves acquiring knowledge, skills, values, and attitudes. The formal form of education in schools provides students with an organized structure and curriculum. The components of national education include the environment, facilities and infrastructure, resources, and society. These components collaborate, establish connections and aid in accomplishing educational objectives. Teachers, and their potential, play a crucial role in the realm of education. The psychological potential of teachers in teaching and learning activities plays a role in improving their teaching. This study aims to evaluate and analyze the effect of using Prezi as a learning medium on the effectiveness of teaching and learning activities at SMK Negeri 1 Girisubo. We collected data using a descriptive qualitative approach, which included interviews, direct observations in class, and document analysis. The results showed that using Prezi significantly increased student engagement, understanding of the material, and learning motivation. Prezi's dynamic and interactive visual displays helped students focus more and understand complex materials better. Despite challenges such as the need for adequate technological infrastructure and additional time for preparation, teachers felt that Prezi provided flexibility and creativity in compiling learning materials. We expect schools with similar characteristics to adopt these practical recommendations for improving the use of Prezi in the teaching and learning process.